Strategic Management Of Diniyah Madrasah In The Development Of Characteristics - Akhmad Aflaha; Ulfiah; Ujang Nurjaman; Ahmad Khori (IJGIE (International Journal of Graduate of Islamic Education), 2022)
Facing the challenges of an era full of changes in various sectors, including globalization, does not abandon the basis of the Qur'an and Sunnah. The current phenomenon is the moral crisis of school children. The demographic bonus era requires graduates who have knowledge, skills and exemplary attitudes. The focus of this research is the strategic management role of Madrasah Diniyah management in an effort to develop morals. This research is a qualitative research with a phenomenological approach. Data collection techniques through observation, interviews and documentation. The subjects were the head of Madrasah, teachers, guardians of students and the community. The object is the management of Madrasah Diniyah in fostering good morals. Data analysis used descriptive type of analysis technique. The conclusion is that the Independent Active Normative Innovative Polite Strategic Management (MANIS) model is the art of utilizing people to carry out work effectively and efficiently through realizing goals, visions and missions through planning, implementation and evaluation. The process of fostering good morals through the methods of understanding, habituation, uswatun hasanah, Targhib and Tarhib (praise and punishment). Through this Strategic Management model, significant results were obtained in increasing the practice of religious, social and cultural values. Madrasah Diniyah are very representative of conducting moral development and almost all students have good morals towards God, teachers and friends in the Madrasah environment.